Child development: vulnerability and resilience - Engle, Patrice L.; Castle, Sarah; Menon, Purnima (International Food Policy Research Institute, 1996)
Many of the challenges facing children now are a function of the changing times, including increases in urbanization, political violence, changing family forms, and, in some a cases, decreased supplies of adequate food. This paper reviews the evolving nature of these risks. In addition, the paper analyzes the development of formal and informal strategies to ameliorate the vulnerability and promote the resilience of young children to these risks. The paper identifies four stages in the research process regarding risks for children: (1) identification of the risk; (2) clarification of etiology and consequences; (3) recognition of resilience among some individuals; and (4) definition of factors in resilience and implications for intervention.